Relationship between Implicit Association Test (IAT) and eye tracker - Chong, Khai Vern; Low, Kah Yue; Teh, Wei Theng (2019)
In Malaysia, racism has been constantly bringing negative impacts to the societal and economic developments. Although Implicit Association Test (IAT) has been widely used to test implicit attitude, researchers still have controversies regarding the validity of IAT. A cross-sectional, experimental design was used to examine whether eye tracker is a valid tool to measure implicit racial attitudes in Malaysia. Convenience sampling was employed to recruit Chinese university students who aged between 18 to 29 years old and with normal or corrected to normal vision. Participants were instructed to complete Race IAT and to read statements that positively or negatively described Malays. After excluding 20 responses due to failure of eye tracker to trace the participants’ eye movements, 50 responses were remained for correlational analyses to examine the relationship between implicit racism scores and the time spent on statements recorded by the eye tracker. Findings revealed that participants with higher implicit racism spent shorter time on reading statements that positively describes Malay, whereas another hypothesis was not supported. One possible cause was that the presence of cognitive load was not taken into considerations during development of hypotheses. This paper also discussed some methodological issues that may contribute to insignificant results such as quality of the statements and high drop-out rates due to the limitations posed by eye tracker. Current result suggested that eye tracker was yet to be validated as a tool to measure implicit racism. Future researches are recommended to improve research design and revise theory used in this study.